Slope stability : a case study of slope failure at Universiti Teknologi Malaysia, Skudai - Gue, Chang Shin (Skudai : Universiti Teknologi Malaysia, 2003)
Project Paper (Sarjana Muda Kejuruteraaan Awam) - Universiti Teknologi Malaysia, 2003